2019
DOI: 10.14202/vetworld.2019.1524-1528
|View full text |Cite
|
Sign up to set email alerts
|

Detection of virulence and multidrug resistance operons in Pseudomonas aeruginosa isolated from Egyptian Baladi sheep and goat

Abstract: Background: Pseudomonas aeruginosa is a pit of an enormous group of free-living bacteria that are able to live everywhere and suggested to be the causative agent of great scope of acute and chronic animal infections. Aim: The current study was carried out to illustrate the prevalence of P. aeruginosa in small ruminants and existence of some virulence operons as well as its antimicrobial resistance. Materials and Methods: A total of 155 samples from sheep and 105 samples from goats (mouth abscesses, fecal swa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
3
6
0
Order By: Relevance
“…The detection rate of tox A and exo S genes in P . aeruginosa from sheep (Dapgh et al, 2019) coincided with our results. The low frequency of tox A and exo S genes in P .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The detection rate of tox A and exo S genes in P . aeruginosa from sheep (Dapgh et al, 2019) coincided with our results. The low frequency of tox A and exo S genes in P .…”
Section: Discussionsupporting
confidence: 93%
“…The frequency of toxA gene in our tested P. aeruginosa isolates from cattle, livestock drinking water and farm workers agreed with Elshafiee et al (2019). The detection rate of toxA and exoS genes in P. aeruginosa from sheep (Dapgh et al, 2019) coincided with our results. The low frequency of toxA and exoS genes in P. aeruginosa from clinically diseased cows (Younis et al, 2015) contradicted the finding of this study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The extracellular pathogenic factors play a key role in P. aeruginosa infection and the most investigated are represented by exotoxin A, phospholipase C, elastase, alkaline protease, and type III secretion system [61]. Few data are available in veterinary literature about the occurrence of these factors in P. aeruginosa clinical isolates from companion [62] and farm animals [63][64][65]. In the present study, a high occurrence was found for all the pathogenic markers that we investigated, suggesting the elevated virulence potential of the isolates, as well as reported in human clinical isolates [66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonasaeruginosa induces various disease conditions in sheep and goats with respiratory illness considered as one of the major issues mainly represented by pneumonia leading to significant mortalities and increased economic losses (Dapgh et al, 2019).…”
mentioning
confidence: 99%